Azobenzene‐Functionalized Metal–Organic Polyhedra for the Optically Responsive Capture and Release of Guest Molecules1. (6th May 2014) - Park, Jinhee; Sun, Lin‐Bing; Chen, Ying‐Pin; Perry, Zachary; Zhou, Hong‐Cai
Abstract Stimuli‐responsive metal–organic polyhedra (srMOPs) functionalized with azobenzene showed UV‐irradiation‐induced isomerization from the insoluble trans‐srMOP to the soluble cis‐srMOP, whereas irradiation with blue light reversed this process. Guest molecules were trapped and released upon cis‐to‐trans and trans‐to‐cis isomerization of the srMOPs, respectively. This study provides a new direction in the ever‐diversifying field of MOPs, while laying the groundwork for a new class of optically responsive materials.